Public goods and decay in networks - Enrique Fatas; Miguel A. Meléndez-Jiménez; Antonio J. Morales; Hector Solaz (SERIEs - Journal of the Spanish Economic Association, 2015)
We propose a simple behavioral model to analyze situations where (1) a group of agents repeatedly plays a public goods game within a network structure and (2) each agent only observes the past behavior of her neighbors, but is affected by the decisions of thewhole group. Themodel assumes that agents are imperfect conditional cooperators, that they infer unobserved contributions assuming imperfect conditional cooperation by others, and that they have some degree of bounded rationality. We show that our model approximates quite accurately regularities derived from public goods game experiments.
Keywords: H41; C92; 330; Public good; Networks; Decay